CONCEPTUAL MODEL FOR IMPROVING THE QUALITY OF THE EDUCATIONAL PROCESS IN AN EDUCATIONAL CLUSTER BASED ON THE NAQSHBANDI TEACHING - Ubaydova, Vazira Erkinovna (SCIENCE and SOCIETY, 2026)
The article analyzes the issue of improving the quality of the educational process within the framework of an educational cluster in harmony with the spiritual-moral, labor-oriented, and socially responsible ideas of the Naqshbandi teaching.
Keywords: educational cluster; Naqshbandi teaching; educational process; quality of education; conceptual model; spiritual education; personality development; cluster cooperation; pedagogical quality; social responsibility